Resilience, skill endowment and diversity: Evidence from US metropolitan areas - Fabrizio Fusillo; Davide Consoli; Francesco Quatraro (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2019)
By adopting the evolutionary approach to resilience, this paper discusses and empirically investigate the determinants of the ability of region to resist, absorb, and react to recessionary shocks. The recent 2008 Great Recession has extremely affected most of the advanced economies all over the World, leading scholars to study in details how different regions responded to the crisis. The aim of the paper is to contribute this literature analyzing the impact of technological, industrial and human capital composition on the short-term resilience. The empirical analysis is conducted on 295 U.S. Metropolitan Statistical Areas over the period 2008-2014. The main finding is that the most resilient regions are those characterized by a very diversified industrial structure. An excess of technological diversity, on the other hand, seems to thwart the ability to absorb external shocks. Lastly, our results suggest that the local occupational structure matters: a high endowment of high-level abstract skills has a positive correlation with regional resilience, though the moderating effect of technological diversity appears to be negative.
Keywords: O18; O3; O51; R11; 330; regional resilience; human capital; technological diversity; industrial diversity